(untitled) (Práxis Educativa, 2022)
In this work, a discussion on the Brazilian legislation that promulgates laws of “treaties” (agreements) is made. Considering the struggles of the Afro-descendant peoples, this legislation was not operationalized, leaving only in the “portrait” (appearances) to meet the political and economic interests of the Brazilian elite with/in their international relations. For this, this study is based on the following laws: Feijó - Law of November 7, 1831; Afonso Arino - Law no. 1,390, of July 3, 1951; Law Caú - Law no. 7,716, of January 5, 1989; 1988 Brazilian Federal Constitution; and Statute of Racial Equality - Law no. 12,288, of July 20, 2010, in dialogue with decolonial theorists to analyze the senses and uses of legal devices regarding racial issues in Brazil. It is argued that these laws exist “just for show” as formal devices of a system that legislates and, at the same time, jettisons the rights of groups such as Afro-descendants in the country. Therefore, there are implications for understanding the contradictions or complex processes of subalternizations of the Afro-descending Brazilian population in force. Keywords: Laws. Racial issue. Decoloniality.